Knowledge Management Plays a Crucial Role in Attaining a Competitive Advantage - saeed, sarkar ahmed; Mohammed, Rebaz Karim; Ahmed, Nawrol Ezzaddin; Aziz, Ershad Mohmmad; Dewi, Asmara (Universitas Islam Negeri Raden Intan Lampung, 2023)
Our research aims to explore the relationship between knowledge management and competitive advantage. We have found that Knowledge and its management can significantly impact achieving sustainable competitive advantage. Organizations must effectively generate, utilize, and distribute Knowledge while integrating it with their processes to maintain this advantage. Additionally, managers must be mindful of acquiring the necessary knowledge to enhance organizational performance and achieve sustainability, thereby gaining an edge over competitors. To ensure long-term competitive advantage, businesses should adopt a comprehensive and integrated approach to creating a knowledge management program. This program should serve as a source of sustainable competitive advantage. It is essential to evaluate the significance of knowledge management within the organization and determine how it can contribute to long-term competitive advantage. Recent research emphasizes the critical role of knowledge management in achieving and maintaining competitive advantage.